Death: a mortal answer - Russell, Thomas (The Stellenbosch Socratic Journal, 2024)
At one time or another every human being will be troubled by death. One may be troubled by the idea of death, or one may be troubled by what death is. Under the idea of death, I include the prospect of death for people one cares about and for oneself; but being troubled by what death is, is to be troubled by the nature or the realisation of death, which is to say what death (being dead) entails for the subject. Of course, those are not two definitively separate concerns. I am interested in something Lucretius is famous for saying about death, that it should not in fact trouble us, and that it only troubles us because we misunderstand something about the nature of death; we think that nonexistence could be bad for us, hence we are right to fear it: all this, says Lucretius, is a mistake arising from misunderstanding death. In this paper I argue that Lucretius is wrong in saying that we should not be troubled by death because (1) the very thing he thinks is irrational to fear is rational to fear, and (2) his argument is self-defeating. In short, (1) annihilation, or the absence of the subject’s point of view anywhere, is a reasonable thing to fear; (2) Lucretius erroneously relies on a conflation of the stateless nature of annihilation with the present experienceable nature of the human being to sustain his conclusion. I conclude that, qua Lucretius’s argument, it is the very loss of the possibility of having possibilities, which fact is entailed simply by being alive, that humans fear, and are quite rational to fear.